Efficacy of combination of antihistaminic agents and blocker of leukotriene receptors in the treatment of pollinosis exacerbation with bronchial asthma attacks. - Y. Dytyatkovska; I. Rodkina; M. Yevtushenko; L. Grybanova; Y. Bendetska; A. Romanova; I. Koretskaia (Medičnì Perspektivi)
We have been observing 60 pollinosis patients at the age of 19 to 64 years with clinical manifestations of rhinitis, conjunctivitis, bronchial asthma. The study was conducted in the design of parallel groups. All patients were divided into 2 clinical groups (main and control), depending on the treatment regimen. The main group included 40 patients who received a combined drug Glencet Advance 1 tab. in the evening for 1 month. 20 patients included in the control group received symptomatic local therapy (eye drops, IGCC), β2-short-acting agonists. Results: integral assessment of symptoms in the main group before treatment was 11.50±0.13 and significantly decreased after treatment to 0.68±0.14 (p<0.001). In the control group differences were much less expressed from 11.15±0.22 before treatment to 3.05±0.29 (p<0.001) after treatment. FEV1 (%) in the main group has been improving more intensively (from 55.5±1.14 to 90.7±1.31 (p<0.01). PEF has been improving from 187.5±4.34 l/sec to 406.3±10.73 (p<0.001). In the control group these changes are less expressed for FEV1 (%) from 56.2±1.72 to 78.5±2.18 (p<0.001). PEF l/sec – (from 195.0±6.75 to 320.0±12.50 (p<0.01)). The histamine level decrease (ng/ml) in the main group was reliable – from 4.29±0.52 to 1.40±0.3 (p<0.5). In the control group – from 3.00±0.33 to 2.82±0.31 (there is no veracious data). Change of the total IgE level in serum: veracious decrease from 487.2 to 367.8 in the main group, no veracious decrease in the control group. Conclusions: the use of combined therapy with antihistamines and antileukotriene drugs in patients with pollinosis gives a good clinical effect, which is confirmed by a veracious decrease of histamine and total IgE levels in blood serum, as well as by veracious improvement in FEV1 and PEF.